Amelioration of excision wounds by topical application of green synthesized, formulated silver and gold nanoparticles in albino Wistar rats - Naraginti, Saraschandra; Kumari, P. Lakshmi; Das, Raunak Kumar; Sivakumar, A.; Patil, Sagar Hindurao; Andhalkar, Vaibhav Vilas (Materials Science & Engineering C-Materials for Biological Applications, 2016)
Wound healing, a complex biological process, has attained a lot of attention as dermatologists are primarily interested in stimulated wound closure without formation of scar or a faint scar. The recent upsurgence of nanotechnology has provided novel therapeutic materials in the form of silver and gold nanoparticles which accelerate the wound healing process. The effect of formulated nanoparticles using Coleus forskohlii root extract (green synthesized) has been tried out for ameliorating full thickness excision wounds in albino Wistar male rats. The evaluation of in vivo activity of nanoparticles in wound healing was carried out on open wounds made by excision on the dorsal sides of albino Wistar rats under anesthesia, and the healing of the wounds was assessed. Histological aspects of the healing process were studied by a HE (Hematoxylin and Eosin) staining method to assess various degrees of re-epithelialization and the linear alignment of the granulation tissue whereas Van Gieson's histochemical staining was performed to observe collagen fibers. The healing action shown by the formulated nanoparticles was remarkable during the early stages of wound healing, which resulted in the substantial reduction of the whole healing period. Topical application of formulated gold nanoparticles was found to be more effective in suppressing inflammation and stimulating re-epithelialization compared to silver nanoparticles during the healing process. The results throw light on the amelioration of excision wounds using nanoparticles which could be a novel therapeutic way of improving wound healing in clinical practice. The mechanism of advanced healing action of both types of nanoparticles could be due to their antimicrobial, antioxidant and anti-inflammatory properties. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: collagen; Gold; green synthesis; Nanopraticles; wound Healing

Diastase induced green synthesis of bilayered reduced graphene oxide and its decoration with gold nanoparticles - Maddinedi, Sireesh Babu; Mandal, Badal Kumar; Patil, Sagar Hindurao; Andhalkar, Vaibhav Vilas; Ranjan, Shivendu; Dasgupta, Nandita (Journal of Photochemistry and Photobiology B-Biology, 2017)
In this paper, we report an enzyme dependent, green one-pot deoxygenation cum decoration method to synthesize diastase-conjugated reduced graphene oxide (DRG) nanosheets, DRG/gold nanoparticles (DRG/Au) composite. The DRG synthesis was completed in 7 h under heating at 90 degrees C on water bath. Selected area electron diffraction (SAED) and Atomic force microscopy (AFM) study has revealed the formation of bilayered reduced graphene oxide sheets. Transmission electron microscopy (TEM) images of DRG/Au composite have shown the uniform decoration of gold nanoparticles (AuNPs) onto the DRG nanosheet surface. Fourier transform infrared spectroscopy (FTIR) and Raman results additionally have shown the functionalization of enzyme molecules onto the DRG nanosheet surface after reduction making it as an effective platform towards the efficient binding of gold nanoparticles. In vitro cytotoxicity studies by MIT assay on A549 and HCT116 cell lines exhibited that the cytotoxicity of the prepared graphene oxide (GO), DRG and DRG/Au is dose dependant. These results have shown that this synthetic method is effective for the production of large scale graphene in a low cost, simple and green method. Since this process avoids the use of hazardous and toxic substances, the produced DRG/Au composites are likely to offer various potential applications in biology and medicine. (C) 2016 Published by Elsevier B.V